(untitled) - FAO (Rome, 1997)
The book presents the results of a survey of the Near East region taken in 1995 and 1996: a regional analysis of water resources and irrigation in the region, and 29 profiles sescribe the situation in each country in more detail
Keywords: irrigation,water supply